Fiz Pol 2020
DOI: 10.56984/8zg2084a3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Training on Muscle Performance and Quality of Life in Patients with Multiple Sclerosis. A Randomized Controlled Trial

Abstract: Background. Compromised muscle performance is common problem in multiple sclerosis (MS) patients and subsequently affects activities of daily living and quality of life (QoL). Objective. to investigate the additional effect of short-term aerobic training on both of muscle performance and QoL in patients with MS. Design. Single blinded, parallel randomized controlled trial. Setting. Faculty of Physical Therapy, Cairo University, Egypt. Participants: 40 patients with relapsing remitting MS (RRMS) were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Non-ablative vaginal erbium laser (VEL; 2940 nm Er:YAG) using the SMOOTH mode technology 3 has been shown to promote the formation of neocollagen in the treated tissue, [4][5][6][7][8] and to restore the tissue structure; 9 resulting in a thickened and strengthened vaginal wall, which offers improved support of the bladder and urethra, 10 and subsequently leads to continence. The positive changes in the structure of the tissue have been used for treatment of SUI, [10][11][12][13][14][15][16][17] vaginal laxity [18][19][20] and symptoms of genitourinary syndrome of menopause (GSM). [21][22][23] Indeed, previous trials using the vaginal erbium laser (VEL) technology have shown promising and consistent results on efficacy and safety 24 with a favorable risk-benefit ratio following treatment; 24 notwithstanding the need for higher data quality from parallel-arm randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Non-ablative vaginal erbium laser (VEL; 2940 nm Er:YAG) using the SMOOTH mode technology 3 has been shown to promote the formation of neocollagen in the treated tissue, [4][5][6][7][8] and to restore the tissue structure; 9 resulting in a thickened and strengthened vaginal wall, which offers improved support of the bladder and urethra, 10 and subsequently leads to continence. The positive changes in the structure of the tissue have been used for treatment of SUI, [10][11][12][13][14][15][16][17] vaginal laxity [18][19][20] and symptoms of genitourinary syndrome of menopause (GSM). [21][22][23] Indeed, previous trials using the vaginal erbium laser (VEL) technology have shown promising and consistent results on efficacy and safety 24 with a favorable risk-benefit ratio following treatment; 24 notwithstanding the need for higher data quality from parallel-arm randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%